Use of ionizing radiation for the inhibition and removal of cyanotoxins in water: A brief review - Thalita Tieko Silva; Sueli Ivone Borrely (Brazilian Journal of Radiation Sciences, 2021)
Cyanobacteria are an ancient and diverse group of microorganisms, considered as important contributors to the formation of Earth's atmosphere and nitrogen fixation. However, the input of nutrients in water by anthropogenic activities frequently provides cyanobacteria blooms associated with toxic compounds. Secondary metabolites, also called cyanotoxins, are often harmful to wild and domestic life, including humans. The first part of this review focuses on cyanobacteria and their ability to produce a variety of toxins as well as describe the Brazilian guidelines on the evaluation and management of these toxins in water quality. Then, we present a review of recent literature on the use of ionizing radiation in terms of cyanobacteria cell removal, degree of degradation of cyanotoxins in water, and reaction kinetics. In view of the exposed results, the paper concludes that ionizing radiation is an efficient and economically viable alternative for the remediation of areas contaminated by cyanobacterial blooms and cyanotoxins, especially in reservoirs intended for water treatment and supply. In addition, some suggestions are provided for further studies on the use of this technology in the treatment of drinking water.